Preliminary Evaluation of Washington State’s Early Intervention Program for First-Episode Psychosis - Oluwoye, Oladunni (Psychiatr Serv, 2019)
OBJECTIVE: Early intervention programs are designed to address the needs of youths experiencing first-episode psychosis (FEP). Washington State developedNew Journeys, a network of coordinated specialty care programs for FEP. In this study, the authors have outlined components of theNewJourneysmodel and preliminary findings since its initial implementation. METHODS: Youths and young adults diagnosed as having psychosis (N=112) completed measures at and after intake on a range of mental health assessments and functional outcomes for the first 12 months of treatment. Administrative data including state-funded emergency department and psychiatric hospitalizations were assessed 24 months before and after intake. Generalized estimating equations were used to assess change over time on multiple measures of mental health status. RESULTS: Compared with their condition at intake, clients had significant decreases in symptoms of anxiety (β=−2.48, p<0.001), psychotic experiences (β=−3.37, p<0.05), and clinician-rated psychotic symptoms (β=−1.47, p<0.05) during treatment. Additionally, quality of life (β=−5.95, p<0.001) and school attendance (odds ratio=1.42, p<0.05) significantly improved during treatment. Administrative data indicated that postintake, clients were less likely to visit the emergency department for psychiatric reasons (β=0.22, p<0.05), utilize community psychiatric inpatient services (β=0.31, p<0.001), and utilize public assistance (β=0.71, p<0.05) compared with 24 months before intake. CONCLUSIONS: New Journeys clients experienced improved clinical and functional outcomes during their first year of treatment, and rates of state-funded service utilization decreased during their treatment.